Alternative solution to synthetic natural gas generation from a source of renewable energy through “Power to Gas” technology (2018)
The present of the gaseous hydrocarbon industry in Colombia is facing a new challenge, the limited availability of reserves and the potential growth in consumption of gas. This is why the country is venturing in alternative sectors that can provide a solution to this situation and allows the innovation in other areas. Power to Gas (PtG) transforms electrical energy into chemical energy through electrolysis. The product obtained from electrolysis is hydrogen and is continuously used in methanation for the production of synthetic methane. The synthetic gas obtained through Power to Gas has similar properties to natural gas and can also be compressed, stored or injected into the same transport and distribution networks. PtG is an alternative to gas generation, through the storage of energy from green technologies.